Anodal transcranial direct current stimulation over the primary motor cortex attenuates capsaicin‐induced dynamic mechanical allodynia and mechanical pain sensitivity in humans. (6th April 2020) - Hughes, Sam W.; Ward, Grace; Strutton, Paul H.
Abstract: Background: Anodal transcranial direct current stimulation over the primary cortex has been shown to activate regions of the brain involved in the descending modulation of pain sensitivity. However, more research is required to dissect the spinal cord analgesic mechanisms associated with the development of central sensitization. Methods: In this randomized, double blind, crossover study 12 healthy participants had baseline mechanical stimulus response (S/R) functions measured before and after the development of capsaicin‐induced ongoing pain sensitivity. The effects of 20 min of either real or sham transcranial direct current stimulation (tDCS, 2 mA) over the primary motor cortex on dynamic mechanical allodynia (DMA) and mechanical pain sensitivity (MPS) were then investigated. Results: Topical application of capsaicin resulted in an increase in area under the pain ratings curve for both DMA ( p < .01) and MPS ( p < .01). The effects of tDCS on the area under the curve ratio (i.e. post‐/pre‐treatment) revealed significant analgesic effects over DMA ( p < .05) and MPS ( p < .05) when compared with sham. Conclusions: This study demonstrates that anodal tDCS over the primary motor cortex can reduce both dynamic and static forms of mechanical pain sensitivity associated with the development of DMA and MPS, respectively. The use of tDCS may provide a novel mechanism‐driven therapy in chronic pain patients with altered mechanical S/R functions. Significance: This research shows new evidence that anodal tDCS over the primary motor cortex can reduce dynamic and static forms of mechanical pain sensitivity in the capsaicin model of ongoing pain. By using this approach, it may be possible to provide mechanism‐driven analgesia in chronic pain patients who have dynamic mechanical allodynia and/or secondary mechanical hyperalgesia.